2021
DOI: 10.1038/s41598-020-80359-1
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of affective contributions to lexical decisions in children and adults

Abstract: The goal of the present study was to investigate whether 6–9-year old children and adults show similar neural responses to affective words. An event-related neuroimaging paradigm was used in which both age cohorts performed the same auditory lexical decision task (LDT). The results show similarities in (auditory) lexico-semantic network activation as well as in areas associated with affective information. In both age cohorts’ activations were stronger for positive than for negative words, thus exhibiting a pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Thus, prediction accuracy increased from RA1 to RA3, but sdewac outperformed all three CL models. This is not surprising since, on the one hand, adults usually perform better in any test than children, and on the other hand, because valence ratings in children are not solely based on the books they read, but also on multiple other sources of information, including their social interactions with adults (Sylvester et al, 2016 , 2021a , b ).…”
Section: Study 4 Predicting Human Rating Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, prediction accuracy increased from RA1 to RA3, but sdewac outperformed all three CL models. This is not surprising since, on the one hand, adults usually perform better in any test than children, and on the other hand, because valence ratings in children are not solely based on the books they read, but also on multiple other sources of information, including their social interactions with adults (Sylvester et al, 2016 , 2021a , b ).…”
Section: Study 4 Predicting Human Rating Datamentioning
confidence: 99%
“…To what extent the present exemplary data can be generalized to other emotion terms and book corpora (e.g., GLEC), and whether they correspond with the development of the emotion term vocabulary in children are key questions for future research. Whereas the neural and affective-cognitive processes underlying the codevelopment of language and emotion is still a badly underresearched area of psychology and the cognitive neurosciences (e.g., Sylvester et al, 2016 , 2021a , b ), a recent study suggests that the emotion vocabulary of children of age 4–11 doubles about every second year (Nook et al, 2017 , 2020 ). According to this study, emotion representations develop from a unidimensional focus on valence to a bidimensional focus on both valence and arousal from age 6 to 25.…”
Section: Study 2 Concrete Abstract and Emotion Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Speech perception and comprehension (e.g., Friederici and Männel, 2013) • Understands role of pointing (e.g., Gredebäck et al, 2010) • Semantic and syntactic sentence processing (Schneider and Maguire, 2019) • Speech discrimination and later grammar (Zhao et al, 2021) • Syntax (Klein et al, 2022) Productive language • Speech imitation (spontaneous) (e.g., Garnier et al, 2013;Kokkinaki and Vitalaki, 2013;Szczepek Reed, 2020) • Adjective generation (e.g., Zhang and Pylkkänen, 2018) • Affective contributions to lexical decisions (e.g., Sylvester et al, 2021) • First and second language speech (e.g., Petitto et al, 2012;Cristia et al, 2014) • From auditory to speech perception (e.g., Dehaene-Lambertz et al, 2005) • High frequency sounds, novel sounds (e.g., Gervain et al, 2016) • Human action sounds vs. other sounds (e.g., Geangu et al, 2015) • Intelligible speech (e.g., Khandaker, 2015;Friederici et al, 2017).…”
Section: Language and Pre-literacymentioning
confidence: 99%
“…Citron et al, 2016a). Differently valenced expressions have also been shown to result in different activation patters in both children and adults (Sylvester et al, 2021) and several studies found metaphors to be more emotional than literal expressions (Gibbs, 2002;Citron and Goldberg, 2014;Mohammad et al, 2016).…”
Section: Psycholinguistic Influence Factors Valencementioning
confidence: 99%